2010
DOI: 10.4161/rna.7.4.12684
|View full text |Cite
|
Sign up to set email alerts
|

A conserved alternative splicing event in plants reveals an ancient exonization of 5S rRNA that regulates TFIIIA

Abstract: To cite this article: W. Brad Barbazuk (2010) A conserved alternative splicing event in plants reveals an ancient exonization of 5S rRNA that regulates TFIIIA, RNA Biology, 7:4,[397][398][399][400][401][402]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…TFIIIA possesses an ExonS event conserved across land plants (Fu et al 2009;Barbazuk 2010). This event was also identified in all species examined in our study.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…TFIIIA possesses an ExonS event conserved across land plants (Fu et al 2009;Barbazuk 2010). This event was also identified in all species examined in our study.…”
Section: Resultsmentioning
confidence: 65%
“…In addition, TFIIIA is connected to the splicing protein network via RNA-binding protein (AT4G35785). TFIIIA has an ExonS event that is conserved across the land plants (Fu et al 2009;Barbazuk 2010). Similar to the network based on TFs in response to stress, we identified a close connection between the R2R3-MYB class with a splicing protein network via TFIID-1 (AT3G13445), and proline-rich spliceosomeassociated family protein (AT4G21660) (Figure 6).…”
Section: R2r3-myb Is Tightly Connected With a Plant-specific Sr Protementioning
confidence: 64%
“…Insertions of the first intron from the UBQ10 gene into intronless genes markedly increased mRNA accumulation over 150-fold (Emami et al, 2013). Recently, plant 5S RNA mimic (discussed above), a naturally occurring alternatively spliced suicide exon (Hammond et al, 2009;Barbazuk, 2010), has been used to regulate gene expression at the premRNA splicing level (Hickey et al, 2012). In this case, skipping of a suicide exon produces a functional transcript, whereas inclusion of this exon generates a transcript that is a target for NMD.…”
Section: Potential Biotechnological Applications Of Asmentioning
confidence: 99%
“…The exon-skipping form encodes the full-length TFIIIA that contains nine ZFs (TFIIIA-9ZF); in contrast, the exoninclusion form has a predicted open reading frame encoding a TFIIIA variant that has only seven ZFs and lacks the first two ZFs of the TFIIIA-9ZF (Supplemental Figure 2). Although it had been initially suggested that the exon-inclusion form of the TFIIIA mRNA may be targeted for degradation (Fu et al, 2009;Hammond et al, 2009), the recent finding that TFIIIA-7ZF protein is present in Arabidopsis (Layat et al, 2012) prompts questions about its biological function and its functional parallels with TFIIIA-9ZF, which is a well established transcription factor for 5S rRNA biogenesis and transport in animals and plants (Barbazuk, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It binds to the internal promoter of 5S rDNA to promote transcription of 5S rRNA and then binds to 5S rRNA to inhibit further transcription as well as to facilitate nuclear export of 5S rRNA for ribosome biogenesis (Klug, 2005). The TFIIIA gene in land plants has evolved a conserved alternative splicing mechanism to generate exon-inclusion and exon-skipping variants (Fu et al, 2009;Hammond et al, 2009;Barbazuk, 2010). The exon-skipping form encodes the full-length TFIIIA that contains nine ZFs (TFIIIA-9ZF); in contrast, the exoninclusion form has a predicted open reading frame encoding a TFIIIA variant that has only seven ZFs and lacks the first two ZFs of the TFIIIA-9ZF (Supplemental Figure 2).…”
Section: Introductionmentioning
confidence: 99%